Ortega and Wittgenstein. Essais on Practical Philosophy - Pérez Monterroso, Victoria (Analysis. Journal of Philosophical Research, 2019)
Book Review: Salas, Jaime y Ariso, José Mª. (Coords.), Ortega y Wittgenstein. Ensayos de filosofía práctica, Madrid: Tecnos, 2018, 344 pp.